What Explains the Difference in Leverage between Banks and Nonbanks? - Berg, Tobias; Gider, Jasmin (Journal of Financial and Quantitative Analysis, 2017)
Banks have much more leverage than nonbanks. In this article, we use a joint sample of banks and nonbanks between 1965 and 2013 to analyze the determinants of this leverage difference. We find that a single factor, asset risk, is able to explain up to 90% of this difference. Banks’ assets consist of a diversified portfolio of nonbank debt. Therefore, banks have much lower asset risk than do nonbanks. Because asset risk is a major determinant of capital structure choice, this factor is able to explain a large fraction of the difference between bank and nonbank leverage.